Study of several aspects of the enzyme tyrosine hydroxylase - Gibson, Sheila M. (University of British Columbia, 2011)
Interest in brain catecholamines has grown considerably in the last few years in view of their possible role as neurotransmitters. This investigation deals primarily with the enzyme tyrosine hydroxylase which is thought to be the rate limiting step in catecholamine synthesis. Using tyrosine hydroxylase measurements and catecholamine depletion techniques,attempts were made to determine the site of increased synthesis of catecholamines in animals exposed to cold. Brain, heart and spleen do not appear to be the organs involved in this change. Adrenals may be of significance but the results were suggestive rather than conclusive. Tyrosine hydroxylase distribution in brain was determined in various regions of rat, rabbit and cat brain, and activity was shown to be highest in the caudate, septal area, nucleus accombens, and anterior perforating substance, with much lower activities in other regions such as hippocampus, amygdala, hypothalamus, thalamus, cortex, cerebellum and brain stem. Using these distribution studies as indications of normal tyrosine hydroxylase activity in areas of rat brain, and electrolytic lesion techniques, studies were carried out to determine noradrenergic and dopanergic pathways in brain. Catecholamine fibers from their origin in the midbrain were traced in the midbrain and diencephalon to the caudate and septal area, and the relative positions of each group of fibers determined along their course. === Medicine, Faculty of === Graduate